(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Chemical and pharmacological investigations have been conducted on the medicinal herbCalendula officinalis Linn. (Asteraceae), which is utilized in traditional medicine in many parts of theglobe. According to chemical analyses, its organs include a wide variety of substances, including butnot limited to volatile oil, carotene, flavonoids, terpenoids, coumarins, quinones, carbohydrates, lipids,amino acids, and other minor elements. C. officinalis extract pure compounds isolated from variousparts of the plant have numerous pharmacological effects, such as anti-inflammatory, antioedematous,anti - oxidant, immunostimulant, and many more. Discuss the antimicrobial properties of Calendulaofficinalis Linn. in this review paper.